2017
DOI: 10.1038/srep41612
|View full text |Cite
|
Sign up to set email alerts
|

LPS-induced inflammatory response is suppressed by Wnt inhibitors, Dickkopf-1 and LGK974

Abstract: In this study, LPS-induced inflammatory responses in BEAS-2B human bronchial epithelial cells and human umbilical vein endothelial cell (HUVEC)s were found to be prevented by Dickkopf-1 (DKK-1), a secreted Wnt antagonist, and LGK974, a small molecular inhibitor of the Wnt secretion. LPS-induced IκB degradation and NF-κB nuclear translocation as well as the expressions of pro-inflammatory genes including IL-6, IL-8, TNF- α, IL-1β, MCP-1, MMP-9, COX-2 and iNOS, were all suppressed by DKK-1 and LGK974 in a dose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 43 publications
6
58
0
Order By: Relevance
“…In this study, IL‐1β expression in the infected macrophages was dependent on Wnt5a. Similar to our research, Jang J et al found that Wnt5a knockdown suppressed LPS‐induced IL‐1β and IL‐6 expression in human bronchial epithelial cells or umbilical vein endothelial cells, and Wu T et al found that nucleoside reverse transcriptase inhibitors up‐regulated IL‐1β, TNF‐α, and IL‐6 in a Wnt5a dependent manner in the central nervous system. Taken together, these observations are consistent with our results that Wnt5a is also involved in the expression of IL‐1β in host immune response.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, IL‐1β expression in the infected macrophages was dependent on Wnt5a. Similar to our research, Jang J et al found that Wnt5a knockdown suppressed LPS‐induced IL‐1β and IL‐6 expression in human bronchial epithelial cells or umbilical vein endothelial cells, and Wu T et al found that nucleoside reverse transcriptase inhibitors up‐regulated IL‐1β, TNF‐α, and IL‐6 in a Wnt5a dependent manner in the central nervous system. Taken together, these observations are consistent with our results that Wnt5a is also involved in the expression of IL‐1β in host immune response.…”
Section: Discussionsupporting
confidence: 90%
“…This study showed that high-glucose culture for 3 days reduced HUVEC viability and NO production, but the damage could be significantly relieved after intervention with OMT or A 2B siRNA. This study has revealed that the expressions of pro-inflammatory genes including TNF-α, IL-6 and IL-1β were increased by LPS-induced inflammatory response in HUVECs [34]. In this study, the results also revealed that IL-1β and TNF-α levels increased significantly due to high glucose, and that OMT could reverse Fig.…”
Section: Discussionsupporting
confidence: 68%
“…A state‐of‐the‐art HUVECs‐based an angiogenic assay was used as a benchmark to test how dynamic culture conditions would impact cell behavior. Indeed, HUVECs can be isolated and maintained by standard protocol with relatively minimal requirements (Baudin, Bruneel, Bosselut, & Vaubourdolle, ; Marin, Kaplanski, Grès, Farnarier, & Bongrand, ) and have been shown responsive to physiological and/or pathological stimuli such as high glucose, lipopolysaccharide (LPS) and shear stress (Jang, Jung, Kim, Jho, & Yoon, ; Patel, Chen, Das, & Kavdia, ; Walshe, dela Paz, & D'Amore, ), thus offering a suitable, general model for endothelial cell both in normal and pathological conditions.…”
Section: Resultsmentioning
confidence: 99%
“…An uneven waste concentration distribution within the medium volume, with higher concentration close to the cell-medium interface was apparent in the static condition; on the other hand uniform waste concentrations/ distributions are obtained in the whole medium volume in the dynamic condition.3.1 | Effect of the dynamic cell culture platform over cell functionalityA state-of-the-art HUVECs-based an angiogenic assay was used as a benchmark to test how dynamic culture conditions would impact cell behavior. Indeed, HUVECs can be isolated and maintained by standard protocol with relatively minimal requirements(Baudin, Bruneel, Bosselut, & Vaubourdolle, 2007;Marin, Kaplanski, Grès, Farnarier, & Bongrand, 2001) and have been shown responsive to physiological and/or pathological stimuli such as high glucose, lipopolysaccharide (LPS) and shear stress(Jang, Jung, Kim, Jho, & Yoon, 2017;Patel, Chen, Das, & Kavdia, 2013;Walshe, dela Paz, & D'Amore, 2013), thus offering a suitable, general model for endothelial cell both in normal and pathological conditions.…”
mentioning
confidence: 99%